Pengelolaan Sampah dan Penanaman Bibit untuk Lingkungan Berkelanjutan - Edettri, Tesa; Anto, Hardi; Vianis, Adittia Okta; Putra, Relissyah; Wijaya, Ermy; Sumantri, Ajis; Elfianty, Lena (Jurnal Gotong Royong, 2026)
Environmental cleanliness and sustainability are important factors in supporting community quality of life. Waste problems are still frequently found in residential areas due to low public awareness and inadequate waste management. This community service activity aims to increase community concern for waste management and environmental preservation through seed planting programs. The method used is a participatory approach involving the community in environmental education, clean-up activities, waste sorting practices, and seed planting around the neighborhood. The results indicate an increase in public awareness in maintaining environmental cleanliness and the formation of positive behavior toward waste management. In addition, seed planting activities contribute to environmental aesthetics and quality. It can be concluded that collaboration between students and the community is effective in creating a clean and sustainable environment.